A Novel Loop-Mediated Isothermal Amplification Assay for Rapid Detection of Yersinia pestis - Bai, Ying; Rizzo, Maria Rosales; Parise, Christina; Maes, Sarah; Eisen, Rebecca J. (Frontiers in Microbiology, 2022)
Rapid detection of Yersinia pestis – the causative agent of plague, is essential during field investigations to enable prompt control measures for prevention of the spread of the disease. Affordable, efficient, reliable, and simple detection assays are extremely useful, particularly in plague-endemic regions with limited resources. We developed a loop mediated isothermal amplification (LAMP) assay that detects Y. pestis within 30 minutes by simply incubating at 65°C on a dry bath heater. The assay targeted the caf1A gene that is situated on the pMT1 plasmid using six specific primers. Y. pestis presence is visually detected based on the color change in the reactions. For comparison of the assay performance, a real-time LAMP with fluorescent dye detection was conducted on a real-time PCR instrument using the same six primers. Sensitivity assessment showed the limit of detection (LOD) was 0.2pg and 0.03pg when performed on the dry bath heater and on the real-time PCR instrument, respectively. The assay was 100% specific having no cross-reactivity with closely related Yersinia spp. and other bacterial species. We tested the LAMP assay on field collected fleas and showed that it successfully detected Y. pestis with identical results to that of a previously published pentaplex real-time PCR assay. These findings suggest the relatively inexpensive and simpler LAMP assay could be used to support field investigations yielding comparable results to more expensive and complex PCR assays.